Transient Elastography Changes on Patient with Hepatic Cirhossis who were Treated by Simvastatin 20 Mg Compared to Simvastatin 10 mg - Endro tanoyo; Neneng Ratnasari; Sutanto Maduseno (Faculty of Medicine Universitas Gadjah Mada, 2020)
Background. Liver cirrhosis is a pathological condition that describes the end stage of liver fibrosis. Fibrosis is currently a two-way process. The process of returning from fibrosis now is a clinical reality. According to Abraldes et al. (2009), administration of simvastatin for one month will increase liver cell regeneration and improve endothelial dysfunction. Liver biopsy is still the gold standard for assessing liver cirrhosis, but this procedure is invasive and has the potential to cause life-threatening complications. Liver biopsy is complicated by sampling errors (reaching 30%) and different abilities between observers. Transient elastography (Fibro scan) is a non-invasive modality for diagnosing liver fibrosis that has high sensitivity and specificity.Aim. The aim of the study was to discover the difference in effect, of simvastatin 20 mg compared to 10 mg for 3 months to improve liver stiffness in patients with liver cirrhosis.Method. The study design used a double blind, randomized clinical trial. The subjects of the study consisted of a group given simvastatin 10 mg / day and the group given simvastatin 20 mg / day for 3 months. Routine medications for cirrhosis were still made according to the original dose. During the study, an initial and final transient elastography examination was carried out and monthly supervision of medication compliance and side effects. Data analysis for statistical tests was carried out by t-test, Mann Whitney test, fisher’s-exact test, and ANOVA test.Result. A total of 21 subjects underwent thorough research and transient elastography. The simvastatin 10mg group (n = 12) experienced a decrease in liver stiffness, with a delta mean of liver stiffness of -4.97+7.09 (p <0.023) compared to the simvastatin 20 mg group (n = 9) with a heart stiffness of -4.09 + 10.06 (p= 0.982). Changed liver stiffness in the two groups were not statistically significant differences. Etiology and confounding drugs showed statistically no significant effect.Conclusion. Both simvastatin 10 mg and 20 mg can reduce liver stiffness. The effect of the two doses of the drug in reducing liver stiffness was not statistically significant different.